2022
DOI: 10.1155/2022/1388225
|View full text |Cite
|
Sign up to set email alerts
|

Comparison Between Real-Time Ultrasound-Guided Percutaneous Tracheostomy and Surgical Tracheostomy in Critically Ill Patients

Abstract: Background. Ultrasound-guided percutaneous dilatational tracheostomy (US-PDT) has been adapted for use in intensive care units (ICU). US-PDT is comparable to bronchoscopy-assisted tracheostomy. However, compared to surgical tracheostomy (ST), its safety and effectiveness have not been well studied. Objectives. To determine the efficacy and safety of US-PDT compared to ST. Materials and Methods. A total of 90 patients who underwent US-PDT (n = 36) or ST (n = 54) between July 2019 and September 2020 were enrolle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…also found that PDT had significantly shorter procedure time than ST (5.2 ± 3.1 vs. 10.5 ± 5.0 min, P < 0.05). [ 3 ] Gupta et al . also reported that the duration of the procedure was significantly lesser in the PDT group than ST group (19.1 ± 11.7 vs. 28.3 ± 18.4 min, P = 0.0001).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…also found that PDT had significantly shorter procedure time than ST (5.2 ± 3.1 vs. 10.5 ± 5.0 min, P < 0.05). [ 3 ] Gupta et al . also reported that the duration of the procedure was significantly lesser in the PDT group than ST group (19.1 ± 11.7 vs. 28.3 ± 18.4 min, P = 0.0001).…”
Section: Discussionmentioning
confidence: 99%
“…The primary benefit of PDT is that it may be carried out at the patient’s bedside in an ICU, reducing surgery, and personnel expenses as well as minimizing the risks associated with transport. [ 2 3 4 ]…”
Section: Introductionmentioning
confidence: 99%
“…However, some authors note that PDT using a bronchoscope has limitations due to the difficulty of accurately identifying the anatomical structures of the neck and preventing complications such as vascular damage 26,27 . Several studies suggest that ultrasound-guided PDT has potential benefits, including portability, safety, identification of cervical vascularity and localization of the tracheal puncture site, reduced procedure time and complications [26][27][28][29][30] . Kang HT et al (2022) concluded in their study that ultrasound-assisted PDT could be offered as an alternative to surgical tracheostomy in high-risk patients 30 .…”
Section: Percutaneus Dilatational Tracheostomy Technicmentioning
confidence: 99%
“…Several studies suggest that ultrasound-guided PDT has potential benefits, including portability, safety, identification of cervical vascularity and localization of the tracheal puncture site, reduced procedure time and complications [26][27][28][29][30] . Kang HT et al (2022) concluded in their study that ultrasound-assisted PDT could be offered as an alternative to surgical tracheostomy in high-risk patients 30 . Protocols proposed in May 2020 for the management of Covid-19 infected patients in the ICU recommend OT as less safe in terms of aerosol spread of the virus compared to PDT, and therefore reduces the potential risk of transmitting a viral infection to medical staff 31 .…”
Section: Percutaneus Dilatational Tracheostomy Technicmentioning
confidence: 99%
“…2 From these studies, it was found that earlier tracheostomy placement can provide benefits in patients who require prolonged mechanical ventilation. [3][4][5] Several factors are known to influence the outcome in patients undergoing tracheostomy. Another study said that age and comorbidities affect the mortality rate in patients who underwent tracheostomy.…”
Section: Introductionmentioning
confidence: 99%